2014
DOI: 10.1007/s11199-014-0408-2
|View full text |Cite
|
Sign up to set email alerts
|

Belly Dance as an Embodying Activity?: A Test of the Embodiment Model of Positive Body Image

Abstract: The study aimed to test Menzel and Levine's (2011) embodiment theory of positive body image in the context of belly dance. Participants were 213 women from Adelaide, South Australia. They comprised 112 belly dancers recruited from two belly dance schools, and a sample of 101 college women who had never participated in belly dance. Participants completed questionnaire measures of positive body image, body dissatisfaction, self-objectification, and enjoyment of sexualization. It was found that belly dancers scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Nonetheless, while much research has tended to emphasize the critical importance of negative body image as a risk factor for disordered eating (e.g., Stice et al, 1998), this study contributes to the growing scientific base suggesting the value of focusing on positive body image characteristics as worthy outcomes to strive towards in and of themselves in promoting health and well-being in addition to their potential links to preventing serious psychological disorders (e.g., Bush et al, 2014;Cotter, Kelly, Mitchell, & Mazzeo, 2015;Homan & Cavanaugh, 2013;Homan & Tylka, 2014;Homan & Tylka, 2015;Tiggemann, Coutts, & Clark, 2014;Wasylkiw & Butler, 2014;Wasylkiw, MacKinnon, & MacLellan, 2012;Webb et al, 2014). Indeed, research has supported body appreciation as a predictor and/or intermediary process in the prediction of a range of health-related criterion variables (e.g., Andrew et al, 2014;Avalos & Tylka, 2006;Augustus-Horvath & Tylka, 2011;Gillen, 2015;see Tylka & Wood-Barcalow, 2015a for an overview).…”
Section: Discussionmentioning
confidence: 88%
“…Nonetheless, while much research has tended to emphasize the critical importance of negative body image as a risk factor for disordered eating (e.g., Stice et al, 1998), this study contributes to the growing scientific base suggesting the value of focusing on positive body image characteristics as worthy outcomes to strive towards in and of themselves in promoting health and well-being in addition to their potential links to preventing serious psychological disorders (e.g., Bush et al, 2014;Cotter, Kelly, Mitchell, & Mazzeo, 2015;Homan & Cavanaugh, 2013;Homan & Tylka, 2014;Homan & Tylka, 2015;Tiggemann, Coutts, & Clark, 2014;Wasylkiw & Butler, 2014;Wasylkiw, MacKinnon, & MacLellan, 2012;Webb et al, 2014). Indeed, research has supported body appreciation as a predictor and/or intermediary process in the prediction of a range of health-related criterion variables (e.g., Andrew et al, 2014;Avalos & Tylka, 2006;Augustus-Horvath & Tylka, 2011;Gillen, 2015;see Tylka & Wood-Barcalow, 2015a for an overview).…”
Section: Discussionmentioning
confidence: 88%
“…There is also evidence that women who participate in embodying activities, such as belly dancing (Tiggemann, Coutts, & Clark, 2014), report higher body appreciation than women who do not engage in these activities. Moreover, the relationship between belly dance participation and positive body image is mediated by lower self-surveillance, supporting an indirect relationship between embodying activities and positive body image (Tiggemann et al, 2014).…”
Section: Models Of Positive Body Imagementioning
confidence: 99%
“…This is particularly appropriate for proposals within Menzel and Levine's embodiment model of positive body image. Cross-sectional comparisons of positive body image between those who do and those who do not participate in potentially embodying activities have been conducted (e.g., Swami & Harris, 2012;Tiggemann et al, 2014). The next step is to examine the impact of these embodying activities experimentally.…”
Section: Running Head: Future Directions 16mentioning
confidence: 99%
See 1 more Smart Citation
“…Tiggeman, Coutts, and Clark (2014) found belly dancing to be an embodying activity that has several benefits for its female practitioners, including positive body image. Moe (2012) found that women in belly dancing classes experienced holistic healingfrom physical illness, injury or disease or emotional or psychological distress -because the classes offered a space in which "to experience something that focuses on women and emphasizes their femininity, rather than preys on or targets it" (p.12).…”
mentioning
confidence: 99%